The determinants of household debts in Asian countries/ Muhammad Amirul Syafiq Asri - Asri, Muhammad Amirul Syafiq (2018)
Household indebtedness problem caused economic slowdown and even financial crisis resulting in global financial instability. High level Of household debt not only resulted in social and family predicament but also emotional and psychological stress. This study analyses the determinants of household indebtedness in Asian countries Which is Malaysia. Brunei, Singapore, South Korea and Australia. This study used descriptive statistics and ordinary least squared method with normality, multiple regression, descriptive analysis unit and correlation. The level of household debt is significantly affected by macroeconomic factors including gross domestic product, interest rate and unemployment rate (Ho, View & Ho,2016).